Lawyer fees, claims and sentence enforcement. An overhaul of the principal of mutual trust between EU states - Lorente Martínez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The rules on the extraterritorial validity of decisions have a very important place in European Union law. They are the rules that culminate in and enhance a European judicial area. They are also rules that enhance legal certainty and international exchange, since they allow individuals, once they obtain a decision in one Member State of the European Union, to enforce it in that State or in another State of the European Union in a swift manner. Including when one of the parties involved is a consumer, as seen in this work.
Keywords: enforcement; consumer; international jurisdiction; European Law; lawyer